Hydroboration of Methyl Esters of Fatty Acids - Ali Mcheik; Akram Hijazi; Hicham Diab; Ahmad Shamseddine (European Scientific Journal, ESJ, 2017)
Hydroboration addition reactions of a boron atom, and hydrogen over unsaturated, have been widely studied. They have excellent access routes to organoborans which have proven to be a very useful synthetic intermediate (Brown et al.; Matteson, 1987; Smith, 1994). The bill might be on one or other of the two carbons of the unsaturation. It is carried out preferentially along the least congested carbon (anti-Markownikov addition). This regioselectivity can be changed against steric effects (Brown & Zweifel, 1960; Brown & Sharp, 1968; Brown et al., 1974). The existence of two active sites in methyl esters of fatty acids, FAME: the carbon-carbon unsaturation and the ester, make their hydroboration reactions more difficult to achieve. However, it has been demonstrated that reducing the ester groups is much slower than that of olefins (Brown & Keblys, 1964). By using suitable operating conditions, it is possible to limit this secondary reaction and to obtain a selective reaction of carboncarbon double bond (Fore & Bickford, 1959). Others have protecting ester function by a silyl group in order to have a single reactive site (Kabalka & Bierer, 1989).